Skinnytaste meal prep : healthy make-ahead meals and freezer recipes to simplify your life - Homolka, Gina; Jones, Heather K (Clarkson Potter/Publishers, 2020)
The best-selling author of The Skinnytaste Cookbook shares more than 120 healthy, diverse convenience recipes that use everyday ingredients for satisfying, high-nutrient freezer foods, minimum-effort suppers and grab-and-go breakfasts and lunches.